2019
DOI: 10.4314/acsj.v27i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pruning and waxing in reducing postharvest physiological deterioration in Uganda local cassava varieties

Abstract: Cassava (Manihot esculenta Crantz) roots in the fresh form, are susceptible to postharvest physiological deterioration (PPD), thus reducing their economic value and farmer benefits. The objective of this study was to evaluate the effectiveness of pruning and waxing on fresh root storability among cassava varieties in Uganda. Sixteen cassava plants per variety (TME 14, NASE 14, Nyaraboke, Kirimumpale, and Bukalasa) were pruned seven days before harvest, leaving the rest as unpruned controls. After harvest, root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…According to Oyeyinka, Ajayi, et al (2019), if these changes are not monitored and controlled through appropriate storage, the quality of resulting products can be negatively affected. Previous studies reported that the spoilage of cassava root can be prevented to a certain extent by storing the roots under a controlled atmosphere condition (Uchechukwu-Agua, Caleb, Manley, & Opara, 2015), waxing (Nuwamanya et al, 2019), refrigeration (Oyeyinka, Salako, et al, 2020; and freezing . Freezing seems to be the best method of preservation of foods since water is practically immobile and unavailable for enzymatic changes within the food structure, although it may result in damage of tissues in cassava roots.…”
Section: Introductionmentioning
confidence: 99%
“…According to Oyeyinka, Ajayi, et al (2019), if these changes are not monitored and controlled through appropriate storage, the quality of resulting products can be negatively affected. Previous studies reported that the spoilage of cassava root can be prevented to a certain extent by storing the roots under a controlled atmosphere condition (Uchechukwu-Agua, Caleb, Manley, & Opara, 2015), waxing (Nuwamanya et al, 2019), refrigeration (Oyeyinka, Salako, et al, 2020; and freezing . Freezing seems to be the best method of preservation of foods since water is practically immobile and unavailable for enzymatic changes within the food structure, although it may result in damage of tissues in cassava roots.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid deterioration that occurs in the root after harvest, several traditional and modern methods of storing have been developed to control the deterioration of cassava roots (Oyeyinka et al, 2019). Cassava roots have been stored using controlled atmosphere (Uchechukwu‐Agua, Caleb, Manley, & Opara, 2015), deep freezing (Oyeyinka et al, 2019; Uchechukwu‐Agua, Caleb, & Opara, 2015), waxing (Nuwamanya et al, 2019), and refrigeration (Cooke, Rickard, & Thompson, 1988; Uchechukwu‐Agua, Caleb, & Opara, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such alternatives include a range of high throughput phenotyping procedures, the most notable of which is near-infrared reflectance spectroscopy (NIRS). 7 Previous studies have recognized NIRS as a robust technique for estimating DMC in cassava roots. [8][9][10] Such studies act as a basis for estimating amylose content and the starch yield.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, alternative and high throughput methods characterized by speed, versatility and precision are required among breeding programs. Such alternatives include a range of high throughput phenotyping procedures, the most notable of which is near‐infrared reflectance spectroscopy (NIRS) 7 …”
Section: Introductionmentioning
confidence: 99%